2018
DOI: 10.3390/foods7080126
|View full text |Cite
|
Sign up to set email alerts
|

Recipes for Determining Doneness in Poultry Do Not Provide Appropriate Information Based on US Government Guidelines

Abstract: Research has shown that consumers use unsafe food handling practices when preparing poultry, which can increase the risk of foodborne illness such as salmonellosis or campylobacteriosis. Recipes from cookbooks, magazines, and the internet commonly are used as sources for consumers to prepare food in homes and the expectation is that food will be safe when prepared. According to the United States Department of Agriculture (USDA), using a thermometer properly is the only way to accurately check for doneness of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Changing consumer behaviors is a slow process, and consumers need good reasons to change longstanding behavior. Strategies for improving behaviors and lowering consumers’ chances of getting foodborne illness are needed [ 17 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Changing consumer behaviors is a slow process, and consumers need good reasons to change longstanding behavior. Strategies for improving behaviors and lowering consumers’ chances of getting foodborne illness are needed [ 17 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These findings reveal a gap in food safety practices in domestic settings that may compromise the microbiological safety of the product. Therefore, it is important to validate the cooking times and temperatures in these recipes (Chambers et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Roughly half of the chicken dishes were considered done when the end point temperature was below 74 • C (grilled chicken: 17/33 dishes, fried chicken: 19/46, roasted: 9/33, boiled: 2/7, and pressure cooked: 0/1). Additionally, a study of 474 poultry recipes found that the most common methods to determine doneness were cooking time (94%) and visual inspection (40%), while only 33.7% provided a specific temperature for doneness (Chambers et al, 2018). Consumers following these recipes may not feel the need to verify the internal temperature of the product if it is not in the recipe.…”
Section: Introductionmentioning
confidence: 99%